A Type I Collagen-Targeted MR Imaging Probe for Staging Fibrosis in Crohn’s Disease - Li, Zhoulei; Lu, Baolan; Lin, Jinjiang; He, Shaofu; Huang, Li; Wang, Yangdi; Meng, Jixin; Li, Ziping; Feng, Shi-Ting; Lin, Shaochun; Mao, Ren; Li, Xue-Hua (Frontiers in Molecular Biosciences, 2021)
Fibrostenosis is a serious complication of Crohn’s disease (CD), affecting approximately one-half of all patients. Surgical resection is the typical clinical end due to ineffective antifibrotic therapy mainly through anti-inflammatory treatment and fibrosis can be reverted only at early stages. Mover, human fibrotic disorders is known to be associated with aging process. Thus, accurate monitoring of the progression of fibrosis is crucial for CD management as well as can be benefit to aging related fibrosis. The excessive deposition of type I collagen (ColI) is the core point in major complications of fibrosis, including that in patients with CD and aging related fibrosis. Therefore, a MR imaging probe (EP-3533) targeted type Ⅰ collagen (ColI) was employed to stage bowel fibrosis in Crohn’s disease (CD) using a rat model and to compare its efficiency with the common MR imaging contrast medium gadopentetatedimeglumine (Gd-DTPA). The bowel fibrotic rat model was established with different degrees of bowel fibrosis, were scanned using a 3.0-T MRI scanner with a specialized animal coil. MRI sequence including T1 mapping and T1-weighed imaging were performed before and after injecting the MRI probe (EP-3533 or Gd-DTPA). The T1 relaxation time (T1 value) and change in the contrast-to-noise ratio (ΔCNR) were measured to evaluate bowel fibrosis. Masson’s trichrome staining was performed to determine the severity of fibrosis. EP-3533 offered a better longitudinal relaxivity (r1) with 67.537 L/mmol•s, which was approximately 13 times that of Gd-DTPA. The T1 value on bowel segments was reduced in the images from EP-3533 compared to that from Gd-DTPA (F=16.478; p<0.001). Additionally, a better correlation between ΔCNR calculated from EP-3533 imaging and bowel fibrosis (AUC=0.846) was determined 10 min after enhanced media administration than with Gd-DTPA (AUC=0.532). The 10th-minute ΔCNR performed using theColI probe showed the best correlation with the severity of bowel fibrosis (r=0.538; p=0.021). Our results demonstrates that targeted MRI probe (EP-3533) supplies a better enhanced effect compared to Gd-DTPA and could be a promising method to evaluate the progression and monitor the therapeutic response of bowel fibrosis.